TIPOLOGI KETERAMPILAN MENULIS AKSARA JAWA SISWA SEKOLAH DASAR DILIHAT DARI TEORI PERKEMBANGAN KOGNITIF BRUNER - Khoirina, Haninda Putri; Fardani, Much Arsyad; Fajrie, Nur (STKIP Persada Khatulistiwa Sintang, 2025)
Cognitive development plays an important role in the learning process of school-aged children, especially during the elementary school years when cognitive growth is most rapid. One aspect of cognitive development is language ability, which includes four language skills, one of which is writing. Writing skills are crucial in language learning, such as in the Javanese language. Writing Javanese script requires advanced writing skills. However, a lack of student interest in learning to write Javanese script has been observed. The purpose of this study is to explore the typology of elementary students' writing skills in Javanese script based on Bruner’s cognitive development theory. This research uses a descriptive qualitative narrative method. Data were collected through observation, interviews, and documentation. The data analysis technique involved data reduction, data presentation, verification, and drawing conclusions. Data validity was ensured using source triangulation. The research subjects were children aged 9–12 years. The object of the study was the writing of Javanese script by children within the framework of Bruner’s cognitive development theory. The results showed that children’s Javanese script writing skills follow the three cognitive learning processes outlined in Bruner’s theory: information acquisition, information transformation, and evaluation.